Entrepreneurship in Society 5.0: integrating technology and humanistic values for a sustainable future: Industry 4.0 and 5.0, Society in the context of Industrial Revolutions, Entrepreneurship in Societies 4.0 and 5.0, Industry and Society 5.0 in Serbia - Đorđević, Luka; Ćoćkalo, Dragan; Bakator, Mihalj; Novaković, Borivoj (Industrija, 2023)
Industry 4.0 brings digitization and automation, increasing efficiency, but causing job loss. Industry 5.0 integrates people and machines to overcome these limitations. Entrepreneurship in Society 4.0 is shaped by digital technologies, while Entrepreneurship in Society 5.0 emphasizes the balance of technology and humanistic values. The adoption of Industry and Society 5.0 is growing, requiring further development of infrastructure and education. The focus of this paper is the analysis of the concept of entrepreneurship 5.0 in society 5.0 and the development of a theoretical model for the improvement of entrepreneurship.
Keywords: Industry 4.0; Industry 5.0; entrepreneurship; Society 4.0; Society 5.0